Unlocking the Potential of Halal Tourism in Bandung City: A Qualitative Analysis of Public Diplomacy and Economic Growth - Putranto, Diyan; Tri , Astuti Marhanani; Amonio, Halawa Frans; Milawati, Milawati; Leonard, Siahaan (Jurnal Multidisiplin Madani, 2024)
In this study, it was discussed about the role of sharia tourism as a means of Indonesian public diplomacy to increase the number of tourist visits and the regional economy, especially in Bandung City which is a sharia tourist destination. The research method used is qualitative with an approach to the concept of public diplomacy and Islamic tourism. The results showed that Indonesia's public diplomacy efforts in promoting itself as a sharia tourist destination have succeeded in attracting foreign tourists, especially Muslim tourists, as well as investment. In addition, sharia tourism has also experienced a positive increase, so that the increase in the number of tourist visits and investment can be used to develop the regional economy, especially in Bandung City as a sharia tourist destination